Dinâmica populacional de Cosmopolites sordidus (Coleoptera: Curculionidae) em bananal, cv. nanicão, em São Miguel do Iguaçu, Pr, e sua susceptibilidade a isolado de Beauveria bassiana - Prestes, Tânia Mari Vicentini (2005)
Cosmopolites Sordidus (Germar, 1824) is considered a pest of economic importance in almost all banana producer countries. Knowing the highest incidence season of the pest, and the occurrence of its natural enemies, mainly entomopathogenic fungus, associated or not to environment factors, makes the development of strategies control that cause little impact on the environment possible. With this in mind, the study of C. sodidus population dynamic in banana plant cultivation of the nanicão cultivar without the use of insecticides was carried in the city of São Miguel do Iguaçu, Paraná, Brazil. A biological experiment with Beauveria bassiana (Bals.) Vuill, originated from the experimental area and from Brazil s Research Centers, was conducted aiming to evaluate C. sordidus pathogenicity. The insect s population fluctuation was evaluated between June 2003 to May 2004 using pseudostem traps. Pseudostem traps durability and attractiveness were observed as well as the occurrence of the entomopathogenic fungus, and the presence of predators. Obtained data was correlated to environmental factors observed during the evaluations. It was observed that C. sordidus population fluctuation was negatively influenced by rain precipitation. Adult population summit occurred in June and July 2003, period of cool temperature and low rain precipitation. C. sordidus larvae summit occurred in December when temperature (29.7ºC) and rain precipitation (308.6 mm) were the highest. Predators were identified as pertaining to following order and family correspondingly: Coleoptera (Carabidae), Dermaptera (Forficulidae), Hemiptera (Reduviidae), Hymenoptera (Ponerinae) and Aranae (Ctenidae, Clubionidae, Lycosidae) which usually feed from C. sordidus eggs and larvae. Predator population summit occurred two months following C. sordidus adult population summit. Although at low incidence, with an annual average of 0.44%, adults infected by B. bassiana were found, where the highest infection indexes occurred in September and October (1.2%). In laboratory conditions all of the B. bassiana isolates caused C. sordidus adult mortality, and there weren t significant statistical differences among them, indicating that they can be utilized for the controlling of pest